Edukasi melalui Buku Saku dan Video Animasi Diabetes Mellitus terhadap Kader Prolanis Kota Pontianak: Education through Pocket Book and Video of Diabetes Mellitus towards Non-Medical Officer of Pontianak City - Hariyanto IH; Hadi Kurniawan; Fajar Nugraha (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The prevalence of diabetes mellitus (DM) was increased in Pontianak. The Technical Implementation Unit (UPT) of Puskesmas Perumnas II, as one of the primary health centers in Pontianak, has applied the Diabetes Mellitus Chronic Disease Management Program (Prolanis) to overcome this problem. The Puskesmas Perumnas II involves non-medical workers through training to serve as officers who assist in implementing the Prolanis program. In this program, Pharmacists provide knowledge for non-medical workers through education and counseling related to DM treatment. In this community service activity (PKM), we aim to educate these non-health officers of Prolanis in Puskesmas Perumnas II regarding the knowledge of prevention and management of diabetes mellitus. As the method, we prepared the timeline activity, including orientation and coordination with Puskesmas Perumnas II, selecting the non-health officers of Prolanis as the participants, providing the materials (pocketbook and video), implementation of activities (conducting pre-tests, materials, and media transfers to participants, discussions, debriefings, post-tests, and evaluation through questionnaires), and data analysis. We found that participants' knowledge was increased related to DM and its treatment based on the average of pre-test and post-test results, such as 59.75 and 73.25, respectively. Evaluation of this education method through questionnaires showed that participants felt the material provided was very interesting, and participants gained new knowledge through the educational media provided.